Penatalaksanaan Fisioterapi Pada Post Operasi Fraktur Colles 1/3 Distal Sinistra Di Rumah Sakit Tentara Dr Soedjono Magelang - Adhe Saputra, Pamungkas; , Yulisna Mutia Sari, SSt. FT., M. Sc. (GRS) (2015)
Background: Colles fracture is trauma that often occurs in the wrist elderly who typically have osteoporosis. Classically these fractures occurred after the fall resting on hands teregang.Garis fractures usually are 2.5 cm proximal side of the wrist and distal fragments migrate to the posterior (deformity resembling a fork when viewed from the side) and to the radial often accompanied by some degree of shortening bone due to impaction some component parts. Physiotherapy in cases of Colles fracture role in reducing motion pain , tenderness , painful silence , and increase muscle strength and joint range of motion (ROM). Objective: To investigate the implementation of physiotherapy for pain relief, increased mobility impairments, and improved functional ability to walk. Methods: Infrared and exercise therapy to reduce pain, limitation of motion, and improve functional ability. Results: Examination conducted by VAS pain is obtained for the silent pain, pain motion, and tenderness, muscle strength, and limited motion changes. On examination of the functional activities with results obtained WHDI: (T1) with a pain intensity score of 3, thick taste and tingling with a score of 4, self-care with a score of 3, the power to score 6, tolerance typing or writing with a score of 6, working with a score of 6, driving with a score of 6, sleeping with a score of 2, homework with a score of 5, and recreation or sport with a score of 6. The amount of the overall with a score of 47 (full dependency). Conclusion: By using infrared modalities and exercise therapy results found no decrease in silent pain, pain in motion, and tenderness, increased range of motion, and increase the functional capabilities.